Co‐infection of Scedosporium apiospermum and Mycobacterium chelonae in an immunocompetent host. Issue 10 (16th September 2014) - Kim, Ji Seok; Choi, Misoo; Nam, Chan Hee; Kim, Jee Young; Hong, Seung Phil; Kim, Myung Hwa; Park, Byung Cheol
Abstract A 75‐year‐old man presented with multiple, scaly, erythematous, grouped papules, nodules and plaques with tenderness ranging from the right forearm to hand dorsum and the right lower leg for 2–3 months. Five months prior to presentation, the patient had received an antibiotic skin test on his right forearm. Lesions appeared approximately 2–3 months after the antibiotic skin test, slowly progressing without clinical improvement. Culture for fungus on the right forearm revealed growth of Scedosporium apiospermum. The tissue acid‐fast bacilli (AFB) culture for the right forearm and right leg revealed growth of non‐tuberculous mycobacteria which was Mycobacterium chelonae, and subsequent tissue polymerase chain reaction of both sites reported positive signs of M. chelonae. On diastase periodic acid‐Schiff stain of the biopsy specimen of the right forearm, fungal hyphae were found while rod‐shaped bacilli could be seen in AFB stain for the biopsy specimen of the right leg. The patient was treated with oral clarithromycin and ciprofloxacin along with an oral antifungal agent for 13 weeks. After the treatment, the lesions subsided and left a scar. We report a rare case of co‐infection of S. apiospermum and M. chelonae in an immunocompetent host.